Issues with families and children in a disaster context: a qualitative perspective from rural Bangladesh - Akhter, Syeda Rezwana; Sarkar, Ratan Kumar; Dutta, Mitul; Khanom, Roxana; Akter, Nasima; Chowdhury, Md. Raihan; Sultan, Mainus (© 2015 Elsevier Ltd., 2016)
This article was published in the International Journal of Disaster Risk Reduction [© 2015 Elsevier Ltd. ] and the definite version is available at : http://doi.org/10.1016/j.ijdrr.2015.07.011. The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S221242091530039X